2000
DOI: 10.1161/01.hyp.36.3.350
|View full text |Cite
|
Sign up to set email alerts
|

Converting Enzyme Inhibition Normalizes QT Interval in Spontaneously Hypertensive Rats

Abstract: Abstract-We quantified the repolarization time (so-called QT interval) in a rat, an animal species that does not show a well-characterized T wave on surface ECG. We used spontaneously hypertensive rats (SHR) and converting enzyme inhibition to demonstrate a reversible increase in QT interval in pressure-overloaded hearts in the absence of ischemia. An implanted telemetry system recording ECG data in freely moving rats was used to automatically calculate the RR interval. The QT duration was manually determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 27 publications
3
21
1
1
Order By: Relevance
“…Such an anomaly might introduce significant errors in a quantitative estimate of MF strength and orientation. Absolute values of cardiac intervals were consistent with those reported in previous ECG and MCG studies (6,13,24,25). Clear-cut age-related changes in the duration of PR, QRS, QT peak , QT end , JT peak , JT end, and T peak-end were found.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Such an anomaly might introduce significant errors in a quantitative estimate of MF strength and orientation. Absolute values of cardiac intervals were consistent with those reported in previous ECG and MCG studies (6,13,24,25). Clear-cut age-related changes in the duration of PR, QRS, QT peak , QT end , JT peak , JT end, and T peak-end were found.…”
Section: Discussionsupporting
confidence: 90%
“…It is well known that aging is associated with morphological and electrical remodeling of the myocardium (3, 34, 45, 58), leading to a higher incidence of life-threatening arrhythmias and sudden death (33,55), especially in the presence of ventricular hypertrophy or other cardiomyopathy (6,25,26,59,67,68). Therefore, the primary aim of this research was to evaluate age-related changes in cardiac intervals and VR parameters calculated from MCG maps, with the influence of sex taken into account (10,13,73).…”
Section: Discussionmentioning
confidence: 99%
“…At the cellular level, ventricular repolarization is prolonged in a number of cardiac disturbances such as myocardial hypertrophy, ischemia or congestive heart failure (1,2,5). Changes of the QT interval have also been described in experimental models of hypertension (28). The other parameters examined in the present study were found to be unchanged by aging.…”
Section: Discussionsupporting
confidence: 60%
“…Stimulation of β-adrenergic receptors by ISO is associated with activation of the transduction mechanisms involving kinases, G proteins, and adenosine nucleotides (Zimmer 1997;Suzuki et al 1998;Zou et al 1999), activation of the renin -angiotensin -aldosterone system (Nagano et al 1992;Golomb et al 1994;Baillard et al 2000;Leenen et al 2001;Rajadurai and Prince 2007), induction of oxidative stress (Zhang et al 2005;Rajadurai and Prince 2007), activation of the Na + /H + exchanger (Ennis et al 2003) and Na + /Ca 2+ exchanger (Chorvatova et al 2004), elevated levels of endothelins (Suzuki et al 1998), or changes in NO production (Krenek et al 2006(Krenek et al , 2009Ribeiro et al 2009), increased expression of fibrogenic factors including, e.g., connective tissue growth factor (CTGF) and NADPH oxidase (NOX4) (Ma et al 2011). Overexpression of β 1 -adrenergic receptors and G s -protein in the murine myocardium (Colluci et al 2000) developed left ventricular dilatation, contractile dysfunction and apoptosis.…”
Section: Introductionmentioning
confidence: 99%